Perspectives on the risk assessment for nongenotoxic carcinogens and tumor promoters. - Perera, F P (1991)
The issue of risk assessment for carcinogens that appear to act via nongenotoxic mechanisms or at the tumor promotion stage, respectively, is discussed in light of current information on biological mechanisms involved in carcinogenesis as well as interindividual variability in human response. Proposals to treat "nongenotoxic" carcinogens and tumor promoters as posing lower risks to humans are described and evaluated. It is concluded that, for purposes of risk assessment and regulation, there is currently no convincing scientific rationale for constructing categories of carcinogens according to their presumed mechanism or stage of action.